RNA Interference as a Vector Control Mechanism: Reducing Aedes albopictus Populations and Disrupting Arbovirus Transmission Cycles - Omokungbe, Bodunrin; Justus Liebig University Giessen (My University, 2025)
Mosquitoes are considered the “most dangerous animals on Earth”. This is not because of the small amount of blood they take from us, but due to the pathogens they can transmit during this process. Key examples are malaria parasites, dengue virus, chikungunya virus, and Zika virus, causing over a million deaths annually. Urbanization, transport, and global trade have led to the spread of invasive species such as the Asian tiger mosquito (Aedes albopictus). Originally from Southeast Asia, this species has migrated to other parts of the world. This mosquito can transmit numerous arboviruses, filarial worms, and bacteria. Conventional control relies on chemical insecticides and biological agents, but off-target effects and resistances limit their usefulness. Therefore, targeted approaches like RNA interference (RNAi) are essential. RNAi is a naturally occurring post-transcriptional gene silencing mechanism in most eukaryotes. Silencing essential genes via RNAi can induce mortality, distort vital phenotypes, and impair the ability to transmit pathogens. This thesis evaluated RNAi as a species-specific control strategy against Ae. albopictus. Prior successes have demonstrated improving RNAi outcome in other mosquito species using transfection reagents (TRs), so I hypothesized that formulating dsRNA with TRs would enhance uptake and efficacy. However, no TRs are specifically designed for long dsRNA in aedine cell lines, and their undisclosed compositions makes selection difficult. Here, I established an RNAi workflow for aedine cell lines and screened multiple TRs for dsRNA delivery. Their complexing capacity and the cytotoxicity of their complexes were assessed. Most of them formed stable complexes, except HiPerFect, which failed even at a 1:9 (dsRNA:TR) ratio. The complexes were mostly non-cytotoxic, but Lipofectamine 2000 exhibited cytotoxic effects at concentrations above 1 ng/μL. Meanwhile, the five most effective TRs increased cellular uptake of long dsRNA and improved RNAi knockdown efficiency in Ae. albopictus U4.4 cells. Furthermore, candidate genes associated with high mortality in other insects were selected and two dsRNA constructs per gene were designed. Initial evaluation in U4.4 cells was conducted with both unformulated and TR-encapsulated dsRNA. Only one dsRNA against inhibitor of apoptosis (IAP) reduced U4.4 cell viability, yet all selected dsRNA showed significant knockdown of the candidate genes by RT-qPCR. Subsequently, I established RNAi workflow for the in vivo assessment in Ae. albopictus, but no dsRNA led to significant larval mortality. The knockdown of IAP gene was observed, but only in dissected gut tissue, and not in the whole body. The lack of larval mortality led to further investigations to identify possible barriers limiting RNAi efficacy. Particle sizing indicated optimal dsRNA:TR complex sizes, but only at lower concentrations. Fluorescence imaging confirmed oral uptake, but no spread of the dsRNA beyond the gut. Ex vivo assays showed rapid dsRNA degradation by larval gut extract, which were identified in Ae. albopictus for the first time and are expressed across larval stages, with the highest expression in gut tissues. The data indicated that the lack of larval mortality was likely due to suboptimal particle size (at higher concentrations), poor systemic spread, and rapid degradation of the selected dsRNA by nucleases. In addition, a standardized protocol was developed to analyze alphavirus replication in aedine cell lines. Viral inhibition was demonstrated with furin inhibitors using a SFV reporter tagged with mCherry as a model. This workflow thereby provides an in vitro platform for evaluating dsRNA against mosquito-borne viruses. Lastly, the feasibility of RNAi to reduce SFV replication in aedine cell line was assessed using the established protocol. For this, dsRNAs were designed and showed no cytotoxicity. Most of the synthesized dsRNAs inhibited virus spread when encapsulated. The dsRNA against non-structural protein 4 (nsp4) reduced viral replication by up to 80%. A concentration of 0.5 ng/μL of the encapsulated dsRNA was enough to significantly suppress the spread of the reporter virus signal. The antiviral effect of nsp4-dsRNA was validated by RT-qPCR, which confirmed a significant knockdown of the target gene. The central hypothesis that encapsulation of dsRNA increases efficacy was supported by most of the cell line experiments. However, the in vitro successes did not translate to in vivo lethality. Therefore, future work should develop optimized formulations to protect dsRNA and promote spread beyond the larval gut. More so, identifying gut-essential genes could enable larval mortality without systemic spread. While suppression of arboviral replication in an aedine cell line was demonstrated here, in vivo validation is still required. A potential RNAi bioinsecticide or arboviral transmission inhibitor must be potent, economical, and highly target-specific. Overall, this thesis presented the first comprehensive analysis of TRs for aedine cells, developed an RNAi workflow for evaluating dsRNA in Ae. albopictus, established a protocol to measure alphavirus infection in real time, and also showed that RNAi can reduce arboviral replication in mosquito cells.
Keywords: ddc:570